A wide input-voltage range quasi-Z source boost DC-DC converter with high voltage-gain for fuel cell vehicles - Zhang, Yun; Fu, Chuanzhi; Sumner, Mark; Wang, Ping (Institute of Electrical and Electronics Engineers, 2018)
A quasi-Z-source Boost DC-DC converter which uses a switched-capacitor is proposed for fuel cell vehicles. The topology can obtain a high voltage gain with a wide input-voltage range, and requires only a low voltage stress across each of the components. The performance of the proposed converter is compared with other converters which use Z-source networks. A scaled-down 400V/400W prototype is developed to validate the proposed technology. The respective variation in the output voltage is avoided when the wide variation in the input voltage happens, due to the PI controller in the voltage loop, and a maximum efficiency of 95.13% is measured.